The Heresy of Relevance: Bonhoeffer's Warning to Preachers - Dean, Robert J. (Pro ecclesia, 2022)
Amid a crisis in biblical interpretation brought to a head by the Church Struggle in Germany, Dietrich Bonhoeffer delivered an address in August 1935 to a group of Confessing Church pastors entitled “Contemporizing New Testament Texts.” Bonhoeffer sounded a clarion call for the retrieval of a thoroughly theological hermeneutic that would liberate preachers for the bold proclamation of the Gospel within a culturally compromised church. This paper will present a reading of Bonhoeffer's daring address that seeks to both situate it within its unique historical context and attend to the ways that it calls into question many of the cherished hermeneutical and homiletical assumptions that dominate contemporary preaching for the sake of a more faithful proclamation of the Gospel of Jesus Christ.